Carbon metabolism of peach fruit after harvest: changes in enzymes involved in organic acid and sugar level modifications - Borsani, Julia (2009)
Peach (Prunus persica L. Batsch) is a climacteric fruit that ripens after harvest, prior to human consumption. Organic acids and soluble sugars contribute to the overall organoleptic quality of fresh peach; thus, the integrated study of the metabolic pathways controlling the levels of these compounds is of great relevance. Therefore, in this work, several metabolites and enzymes involved in carbon metabolism were analysed during the post-harvest ripening of peach fruit cv ‘Dixiland’. Depending on the enzyme studied, activity, protein level by western blot, or transcript level by quantitative real time-PCR were analysed. Even though sorbitol did not accumulate at a high level in relation to sucrose at harvest, it was rapidly consumed once the fruit was separated from the tree. During the ripening process, sucrose degradation was accompanied by an increase of glucose and fructose. Specific transcripts encoding neutral invertases (NIs) were up-regulated or down-regulated, indicating differential functions for each putative NI isoform. Phosphoenolpyruvate carboxylase was markedly induced, and may participate as a glycolytic shunt, since the malate level did not increase during post-harvest ripening. The fermentative pathway was highly induced, with increases in both the acetaldehyde level and the enzymes involved in this process. In addition, proteins differentially expressed during the post-harvest ripening process were also analysed. Overall, the present study identified enzymes and pathways operating during the post-harvest ripening of peach fruit, which may contribute to further identification of varieties with altered levels of enzymes/metabolites or in the evaluation of post-harvest treatments to produce fruit of better organoleptic attributes.